Multifunctional coating with functions of flame retardance, bacteriostasis and electromagnetic shielding as well as preparation and application of multifunctional coating
Through the coordinated use of the flame retardant solution combined with phosphorylated sodium alginate and MXene and the antibacterial solution of mesoporous silica adsorbing pepper essential oil, combined with polyvinylpyrrolidone and the electromagnetic shielding layer sprayed with MXene solution, the problem of improving the versatility of cotton fabrics is solved, and the synergistic effect of flame retardant, antibacterial and electromagnetic shielding is achieved.
Patent Information
- Application Number
- CN202411683351.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art is difficult to effectively realize the versatility of flame retardant, antibacterial and electromagnetic shielding on cotton fabrics, and traditional flame retardant agents have problems such as poor compatibility, uneven dispersion and low flame retardant efficiency.
The flame retardant solution is prepared by combining phosphorylated sodium alginate with MXene, and the bacterial antibacterial solution is prepared with mesoporous silica adsorbing pepper essential oil. Combined with polyvinylpyrrolidone, a flame retardant and antibacterial composite solution is formed. After the padding treatment, the MXene solution is sprayed as an electromagnetic shielding layer to achieve versatility.
The fire retardant, antibacterial and electromagnetic shielding functions of cotton fabrics have been synergistically improved, and the fire safety, antibacterial and electromagnetic shielding properties of the fabrics have been enhanced, and the process is relatively simple and controllable.
Smart Images

Figure CN119553492A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multifunctional coating with the functions of flame retardancy, antibacterial and electromagnetic shielding, and preparation and application thereof, belonging to the technical field of textiles. Background Art
[0002] Cotton fabrics play an important role in people's lives but are extremely easy to ignite. Compared with other substrates such as resins, fabrics are more difficult to make flame retardant due to the weight gain limit of flame retardants. Therefore, it is very important to effectively impart flame retardancy to cotton fabrics.
[0003] At present, flame retardants commonly used in cotton fabrics can be classified into halogen-containing, boron-containing, silicon-containing, nitrogen-containing and metal hydroxide-containing according to different flame retardant elements. Halogen-based flame retardants are gradually being replaced due to their biological toxicity. Boron-based flame retardants are limited in their application on fabrics due to their poor water washability. Silicon-based flame retardants have low flame retardant efficiency and require a large amount of addition when used alone. Similarly, nitrogen-based flame retardants have low efficiency when used alone. Metal hydroxides have poor compatibility with polymer matrices, and adding a large amount will affect the feel and mechanical properties of the fabric.
[0004] The document (International Journal of Biological Macromolecules 272 (2024) 132639) uses layer-by-layer self-assembly technology to improve the fire safety performance of cotton fabrics by phosphorylated bio-based materials and two-dimensional layered nanomaterials, but this method is complicated and time-consuming and labor-intensive, which is not conducive to industrial production, the loading rate is uncontrollable, and the flame retardant efficiency is not high. Patent CN 115322443B reports the use of MXene and the introduction of chitosan to enhance the flame retardant properties and thermal stability of phosphorylated cellulose nanofibrils, but the various substances do not produce chemical grafting through simple physical blending. Although this simple blending method can improve the flame retardant properties of the material by adding a variety of flame retardants, this method often has problems of uneven dispersion and poor compatibility, which limits the further improvement of flame retardant properties. In addition, physically mixed flame retardants may not be able to form an effective interaction with the polymer substrate at the molecular level, resulting in unsatisfactory flame retardant properties.
[0005] Since multifunctional textiles need to maintain their inherent excellent properties and have other functions, when designing such products, it is necessary to consider the coordination and promotion between multiple functions to ensure that they do not interfere with each other. When preparing multifunctional textiles, it is also necessary to consider the environmental stability of the material to ensure that its functions do not degrade under different conditions. Such products are often technically difficult, so there are fewer such products on the market. Summary of the invention
[0006] In order to solve the above problems, the present invention first prepares a flame retardant solution by combining phosphorylated sodium alginate with MXene, and immerses the fabric into the solution to obtain a fabric with flame retardant function; uses mesoporous silica to adsorb prickly ash essential oil to prepare an antibacterial solution, mixes the flame retardant solution, the antibacterial solution, and polyvinyl pyrrolidone to obtain a flame retardant and antibacterial composite solution, and immerses the fabric into the flame retardant and antibacterial composite solution to obtain a fabric with both flame retardant and antibacterial functions; sprays MXene solution on the fabric with both flame retardant and antibacterial functions as an enhanced electromagnetic shielding layer to prepare a multifunctional fabric with both flame retardancy, antibacterial function, and electromagnetic shielding.
[0007] The first object of the present invention is to provide a method for preparing a fabric having a flame retardant function, comprising the following steps:
[0008] (1) MXene and a phosphorylating agent are mixed in a mass ratio of 1:(1-26), heated, and stirred, and then sodium alginate and urea are added, and the mixture is further heated, stirred, and cooled to obtain a mixture;
[0009] The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12);
[0010] (2) purifying the mixture and precipitating the precipitate, washing, centrifuging, and drying the precipitate to obtain a phosphorylated sodium alginate-modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate-modified MXene solution;
[0011] (3) The fabric is dipped into a phosphorylated sodium alginate modified MXene solution and dried to obtain a fabric with flame retardant function.
[0012] In one embodiment, the phosphorylating agent is H 3 PO 4 , H 3 PO 3 , P 2 O 5 POCl 3 , C 6 H 7 O 3 P, NH 4 H 2 PO 4 NH 4 ) 2 HPO 4 , phosphoric anhydride, and one or more of organic phosphates.
[0013] In one embodiment, in step (1), the MXene preparation comprises the following steps:
[0014] Mix lithium fluoride and hydrochloric acid in a mass ratio of 1: (1-8): 1, and add Ti 3 AlC 2 , heating at 30-50° C. for 40-50 h to obtain an etchant;
[0015] The etchant is washed, centrifuged at 4000-6000 r / min for 8-15 min, and the supernatant is taken to obtain a MXene solution;
[0016] The MXene solution was centrifuged at 8000-12000 rpm for 6-10 min, and the supernatant was discarded to obtain MXene.
[0017] In one embodiment, the mass concentration of the MXene solution is 10 to 20 mg / mL, preferably 15 mg / mL.
[0018] In one embodiment, in step (1), MXene and the phosphorylating agent are first dissolved and dispersed, stirred at 40-80° C. for 5-15 min, sodium alginate and urea are added, stirred at 100-150° C. at 200-300 rpm for 2-4 h, and cooled to 20-28° C. to obtain a mixture.
[0019] In one embodiment, in step (2), the mixture is purified and precipitated, the precipitate is washed, centrifuged at 8000-10000 r / min for 6-10 min, and dried at 60-80° C. for 10-15 h to obtain phosphorylated sodium alginate modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate modified MXene solution.
[0020] In one embodiment, in step (3), the fabric can be pretreated as needed, and the pretreatment process includes keeping it in an alkaline solution at 80-120° C. for 50-70 minutes, washing it at 20-28° C. for 1-5 minutes, and then drying it at 40-50° C. until it is completely dry.
[0021] In one embodiment, in step (3), the fabric is immersed in a phosphorylated sodium alginate modified MXene solution for 4 to 10 minutes, and then pad-dried at 50 to 80° C. to a constant weight to obtain a fabric with flame retardant function.
[0022] The second object of the present invention is to provide a flame retardant fabric prepared by the above method.
[0023] In one embodiment, the fabric includes natural fabric and synthetic fabric, wherein the natural fabric is one of silk, wool, linen or cotton fabric; the synthetic fabric is one of polyester fiber fabric, polyamide fiber fabric and polyacrylonitrile fiber fabric.
[0024] The third object of the present invention is to provide a method for preparing a fabric having both flame retardant and antibacterial functions, wherein the preparation method comprises mixing a phosphorylated sodium alginate modified MXene solution, an antibacterial agent solution, and polyvinyl pyrrolidone in a mass ratio of (1-5):(1-5):(0.2-1) to obtain a flame retardant and antibacterial composite solution, and then immersing the fabric in the flame retardant and antibacterial composite solution, and drying to obtain a fabric having both flame retardant and antibacterial functions;
[0025] The method for preparing the phosphorylated sodium alginate modified MXene solution comprises the following steps:
[0026] (1) Mixing MXene and a phosphorylating agent in a mass ratio of 1:(1-26), heating, stirring, then adding sodium alginate and urea, continuing to heat, stir, and cool to obtain a mixture;
[0027] The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12);
[0028] (2) The mixture is purified and precipitated, and the precipitate is washed, centrifuged, and dried to obtain phosphorylated sodium alginate modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate modified MXene solution.
[0029] In one embodiment, the method for preparing the antibacterial agent solution comprises the following steps:
[0030] Dispersing mesoporous silica in a solvent, then adding prickly ash essential oil and polyvinyl pyrrolidone, mixing, separating and purifying to obtain an antibacterial agent solution;
[0031] The mass ratio of the mesoporous silica, the prickly ash essential oil and the polyvinyl pyrrolidone is 1:(0.5-3):(0.05-0.2).
[0032] In one embodiment, the solvent is chloroform; and the solid content of the antibacterial agent solution is 1-2 wt %.
[0033] The fourth object of the present invention is to provide a fabric prepared by the above preparation method and having both flame retardant and antibacterial functions.
[0034] The fifth object of the present invention is to provide a method for preparing a multifunctional fabric with flame retardancy, antibacterial properties and electromagnetic shielding properties. The preparation method comprises coating a MXene solution on the surface of the fabric with flame retardancy and antibacterial properties prepared by the above preparation method or in the present invention as an enhanced electromagnetic shielding layer to obtain a multifunctional fabric with flame retardancy, antibacterial properties and electromagnetic shielding properties.
[0035] The sixth object of the present invention is to provide a multifunctional fabric prepared by the above preparation method, which has the characteristics of flame retardancy, antibacterial and electromagnetic shielding.
[0036] The seventh object of the present invention is to provide the fabric with flame retardant function, the fabric with both flame retardant and antibacterial functions, and the multifunctional fabric with both flame retardant, antibacterial and electromagnetic shielding functions in the present invention for use in the fields of home furnishing, medical protection and electronic communication equipment protection.
[0037] The eighth object of the present invention is to provide a method for simultaneously improving the flame retardant properties, antibacterial properties, and electromagnetic shielding properties of a fabric, comprising the following steps:
[0038] (1) Mixing MXene and a phosphorylating agent in a mass ratio of 1:(1-26), heating, stirring, then adding sodium alginate and a catalyst, continuing to heat, stir, and cool to obtain a mixture;
[0039] The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12);
[0040] (2) purifying the mixture and precipitating the precipitate, washing, centrifuging, and drying the precipitate to obtain a phosphorylated sodium alginate-modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate-modified MXene solution;
[0041] (3) mixing a phosphorylated sodium alginate modified MXene solution, an antibacterial agent solution, and polyvinyl pyrrolidone in a mass ratio of (1-5):(1-5):(0.2-1) to obtain a flame retardant and antibacterial composite solution, and then immersing the fabric in the flame retardant and antibacterial composite solution, and drying to obtain a fabric with both flame retardant and antibacterial functions;
[0042] (4) MXene solution is coated on the surface of the fabric with flame retardant and antibacterial functions as an enhanced electromagnetic shielding layer to obtain a multifunctional fabric with flame retardant, antibacterial and electromagnetic shielding functions.
[0043] In one embodiment, the method for preparing the antibacterial agent solution comprises the following steps:
[0044] Dispersing mesoporous silica in a solvent, then adding prickly ash essential oil and polyvinyl pyrrolidone, mixing, separating and purifying to obtain an antibacterial agent solution;
[0045] The mass ratio of the mesoporous silica, the prickly ash essential oil and the polyvinyl pyrrolidone is 1:(0.5-3):(0.05-0.2).
[0046] In one embodiment, the solvent is chloroform; and the solid content of the antibacterial agent solution is 1-2 wt %.
[0047] Beneficial Effects
[0048] (1) In the present invention, the flame retardant solution prepared by combining phosphorylated sodium alginate and MXene, the active groups such as carboxyl and hydroxyl groups on the surface of sodium alginate and the oxygen-containing groups on the surface of MXene can provide abundant reaction sites for the combination of the two. Phosphorylated sodium alginate can also serve as an acid source and a carbon source, and together with MXene, it constitutes a new intumescent flame retardant system, and the two are closely combined;
[0049] (2) The chemical grafting method used in the present invention can effectively introduce flame retardant elements to improve the flame retardant efficiency, and at the same time can improve the binding force and compatibility between MXene and the phosphorylated sodium alginate matrix. In addition, the flame retardant solution and the antibacterial agent solution of the present invention both use bio-based materials, which have the advantages of wide sources, low prices, green environmental protection and degradability;
[0050] (3) The flame retardant solution of the present invention can be used as a flame retardant coating, which is an organic-inorganic hybrid composite coating, wherein the inorganic two-dimensional nanomaterial MXene has high thermal stability and a large specific surface area, so that it has a strong physical barrier effect, which is beneficial to reduce the transfer of heat and mass; the flame retardant coating also adds electromagnetic shielding function to the substrate, broadening the application field of the material;
[0051] (4) The antibacterial agent solution of the present invention can be used as an antibacterial coating, wherein the mesoporous silica is used as an adsorption material to adsorb the antibacterial and mildew-proof essential oil while having a sustained release effect, thereby achieving a highly efficient and long-lasting antibacterial and mildew-proof effect;
[0052] (5) The flame retardant solution and the antibacterial agent solution of the present invention exert a synergistic effect. The bio-based component (phosphorylated sodium alginate) in the flame retardant solution also exerts an antibacterial effect, and the mesoporous silica in the antibacterial agent solution also has a flame retardant effect. The two synergistically constitute a highly efficient flame retardant and antibacterial solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Surface FE-SEM images of MXene (PSA@MXene) cotton fabric modified with sodium alginate before and after flame retardant finishing at different magnifications; (a1) to (a3) are pure cotton fabrics at 30, 600, and 1500 magnifications; (b1) to (b3) are fabrics (CT-MPS-1) with a 5% weight increase of the flame retardant relative to the original cotton fabric at 30, 600, and 1500 magnifications; (c1) to (c3) are fabrics (CT-MPS-2) with a 10% weight increase of the flame retardant relative to the original cotton fabric at 30, 600, and 1500 magnifications; (d1) to (d3) are fabrics (CT-MPS-3) with a 15% weight increase of the flame retardant relative to the original cotton fabric at 30, 600, and 1500 magnifications.
[0054] Figure 2 The following are surface FE-SEM images of phosphorylated chitosan modified MXene (PC@MXene) cotton fabrics before and after flame retardant finishing at different magnifications; (a)(b)(c) are pure cotton fabrics at 30, 600, and 1500 magnifications; (d)(e)(f) are fabrics (CT-MPC-1) with a 5% weight increase of the flame retardant relative to the original cotton fabric at 60, 600, and 3000 magnifications; (g)(h)(i) are fabrics (CT-MPC-2) with a 10% weight increase of the flame retardant relative to the original cotton fabric at 60, 600, and 3000 magnifications; (j)(k)(l) are fabrics (CT-MPC-3) with a 15% weight increase of the flame retardant relative to the original cotton fabric at 60, 600, and 3000 magnifications.
[0055] Figure 3 Figure 2 shows the TGA graphs of MXene (PSA@MXene) cotton fabric modified with sodium alginate before and after flame retardant finishing. (a) is the TGA graph under Air; (b) is the DTG graph under Air; (c) is the N 2 TGA diagram below; (d) is N 2 Below is the DTG chart.
[0056] Figure 4 Figure 2 shows the TGA graph of phosphorylated chitosan modified MXene (PC@MXene) cotton fabric before and after flame retardant finishing; (a) is the TGA graph under Air; (b) is the TGA graph under N 2 DTG diagram below; (c) is N 2 (d) is the DTG graph under Air.
[0057] Figure 5 Vertical combustion diagram of MXene (PSA@MXene) cotton fabric modified with sodium alginate before and after flame retardant finishing; (a) is pure cotton fabric; (b) is fabric with 5% weight increase of flame retardant relative to the original cotton fabric (CT-MPS-1); (c) is fabric with 10% weight increase of flame retardant relative to the original cotton fabric (CT-MPS-2); (d) is fabric with 15% weight increase of flame retardant relative to the original cotton fabric (CT-MPS-3).
[0058] Figure 6 Vertical combustion diagram of phosphorylated chitosan modified MXene (PC@MXene) cotton fabric before and after flame retardant finishing; among them, (a) is pure cotton fabric; (b) is fabric with 5% weight increase of flame retardant relative to the original cotton fabric (CT-MPC-1); (c) is fabric with 10% weight increase of flame retardant relative to the original cotton fabric (CT-MPC-2); (d) is fabric with 15% weight increase of flame retardant relative to the original cotton fabric (CT-MPC-3). DETAILED DESCRIPTION
[0059] 1. The detection methods involved in the following embodiments include the following:
[0060] (1) SEM
[0061] The morphology of the composite materials was observed using a scanning electron microscope and electron photographs were taken.
[0062] (2) Thermogravimetric analysis
[0063] The thermal degradation and thermal oxidation degradation properties of the fabric were studied using a TGA tester in a nitrogen atmosphere and an air atmosphere, respectively. The heating rate was 20°C / min, the air flow rate was 25mL / min, and the recorded temperature range was 30-800°C.
[0064] (3) Vertical combustion
[0065] The test was carried out according to the GB / T5455-2014 standard method, and the sample size was 300mm×89mm. The flame was applied twice to the bottom of the vertically placed sample for 12s, and the combustion phenomenon was recorded to evaluate the combustion grade of the material.
[0066] (4) Antibacterial performance test
[0067] The test was carried out according to GB / T 20944.3-2008 standard method.
[0068] Bacterial culture: Take 0.1 mL of pre-activated bacterial solution (Staphylococcus aureus and Escherichia coli) and put it into a sterilized shaking tube, add 7-8 mL of bacterial culture solution, and place it in a constant temperature air bath shaker at 37°C and culture it at 100 rpm overnight until the bacteria grow to an appropriate concentration (1-3×10 8 CFU / mL), at this time, the absorbance of OD600 measured by the microplate reader is 0.3-0.4 (Staphylococcus aureus) or 0.25-0.35 (Escherichia coli). If the absorbance is too low, continue to culture to the appropriate concentration; if the absorbance is too high, add culture medium to the bacterial solution to dilute the concentration of the bacterial solution. After the culture is completed, take 2mL of bacterial solution and put it into a 5mL centrifuge tube and put it into a centrifuge and centrifuge it at 8000rpm for 10min. After the centrifugation is completed, pour the supernatant to retain the bacterial sediment in the lower layer, add an equal amount of phosphate (PBS) buffer, vortex for 15s until there is no obvious granular matter in the solution, and resuspend and evenly disperse the bacteria.
[0069] Sample testing: First, each group of samples was sterilized in an autoclave at high temperature, and 37.5 mg (5 mm × 5 mm) of the sterilized sample was placed in each sterile shaking tube. Subsequently, the above bacterial solution was diluted 100 times to 1-3 × 10 6CFU / mL was used as the inoculated bacterial solution for the antibacterial experiment. 3.5mL PBS buffer and 250μL test bacterial solution were added to each shaking tube, and the tube was placed in a constant temperature air bath shaker at 37°C and cultured at 150rpm for 18h. After the incubation, vortex for 30s to resuspend the bacteria, take 0.1mL of the mixed bacterial solution and add it to a 1.5mL centrifuge tube, then add 0.9mL PBS buffer, and dilute it four times in a gradient of 1:10. After the dilution, take 25μL of bacterial solution from each centrifuge tube and gently drop it on the surface of the culture medium. After the four gradient drops are completed, gently shake the culture medium plate, and then place it in a constant temperature incubator at 37°C for 24h until the colonies are clearly visible.
[0070] (5) Electromagnetic energy shielding performance test
[0071] According to ASTM D 4935-89, the S parameters of the sample in the 8-12 GHz region (X band) were measured using a vector network analyzer (DRW0118 model, Beijing Dingrong Shichuang Technology Co., Ltd.) The sample size was 40 mm × 40 mm.
[0072] 2. Raw materials used in the following examples and comparative examples:
[0073] Phosphorous acid, sodium alginate, chitosan, cellulose (cellulose powder, particle size of 50 μm), urea, polyvinyl pyrrolidone, mesoporous silica, ammonium polyphosphate, polyethylene glycol (average molecular weight of 400), and hexadecyltrimethylammonium bromide were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0074] Phosphoric acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. as a phosphoric acid solution (85%).
[0075] Zanthoxylum bungeanum essential oil was purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0076] The preparation method of MXene is as follows:
[0077] (1) Mix 30 mL of concentrated hydrochloric acid and 10 mL of water to obtain a 9 M hydrochloric acid solution;
[0078] (2) Add 2 g of lithium fluoride to the hydrochloric acid solution obtained in step (1), mix for 5 min, and then add 2 g of lithium fluoride to the hydrochloric acid solution. 3 AlC 2 Ti was added in a mass ratio of 1:1 3 AlC 2 Powder, react at 40°C for 48h to obtain an etchant;
[0079] (3) The etchant was washed with deionized water until the solution pH = 7.0, centrifuged at 5000 r / min for 10 min, and the upper layer of liquid was taken to obtain the MXene solution.
[0080] (4) Deionized water is added to or removed from the obtained MXene solution to obtain a MXene solution with a mass concentration of 15 mg / mL, which is centrifuged at 10,000 rpm for 8 min, and the supernatant is discarded to obtain MXene.
[0081] The mass of MXene involved in the examples and comparative examples refers to the solid content; the reaction temperature not specifically specified refers to room temperature, which here refers to 20-30°C; the solution not specifically specified with the solvent refers to water as the solvent.
[0082] Fabric: cotton fabric, average weight 195g / m 2 , purchased from Shaoxing Aobang Technology Co., Ltd.
[0083] Fabric pretreatment:
[0084] Put the cotton fabric into 20g / L sodium hydroxide solution, adjust the temperature to 100℃ and keep it for 60min, then wash it with water at 25℃ for 4min to wash away the residual alkali in the fabric, adjust the oven temperature to 45℃, and bake it for about 60min until it is completely dry.
[0085] Weight gain; the percentage of mass added relative to the fabric itself.
[0086] Spraying amount: percentage relative to the mass of the fabric itself.
[0087] Example 1: Preparation of flame retardant fabric
[0088] 1. Preparation of phosphorylated sodium alginate modified MXene (PSA@MXene)
[0089] (1) MXene and phosphoric acid were dissolved and dispersed uniformly in phosphoric acid at a mass ratio of 1:13, and after being uniformly dispersed, they were added into a 150 mL three-necked flask and stirred at 60°C for 10 min; SA and urea were added into the three-necked flask respectively, and stirred at 250 rpm at 120°C for 3 h, and then cooled to 25°C to obtain a reaction mixture; wherein the mass ratio of MXene, phosphoric acid, SA, and urea was 1:13:1:6;
[0090] (2) The reaction mixture obtained in step (1) was poured into 100 mL of anhydrous ethanol for purification and precipitation. The precipitate was washed with ethanol three times and then with acetone twice, and centrifuged at 9000 r / min for 8 min to obtain a precipitate. The precipitate was vacuum dried at 80° C. for 12 h to obtain phosphorylated sodium alginate modified MXene (PSA@MXene) powder. The PSA@MXene powder was dissolved in deionized water to obtain a PSA@MXene solution with a solid content of 1.5 wt%.
[0091] 2. Preparation of flame retardant fabrics
[0092] The pretreated cotton fabric was immersed in the PSA@MXene solution for 6 min and then dried at 60 °C to constant weight to obtain a cotton fabric with flame retardant function (CT-MPS).
[0093] By adjusting the dosage of PSA@MXene solution, flame-retardant cotton fabrics with weight gains of 5%, 10%, and 15% relative to the original cotton fabric were obtained, which were recorded as CT-MPS-1, CT-MPS-2, and CT-MPS-3, respectively.
[0094] Comparative Example 1: Effect of raw material ratio on the preparation of flame retardant fabrics
[0095] Specific implementation method The CT-MPS-2 with a weight increase of 10% relative to the original cotton fabric in Example 1 is different in that the mass ratios of MXene, phosphoric acid, SA, and urea are adjusted to 1:26:2:12 and 1:1:0.1:0.6, and other conditions remain unchanged to prepare cotton fabric with flame retardant function.
[0096] Comparative Example 2: Effect of the order of raw material addition on the preparation of phosphorylated sodium alginate modified MXene (PSA@MXene) solution
[0097] The specific implementation method is the same as that of Example 1, except that a different order of adding raw materials is adopted, and other conditions remain unchanged;
[0098] The preparation of PSA@MXene solution specifically includes the following scheme:
[0099] Solution 1: Dissolve MXene and urea evenly, stir at 60°C for 10 min, add phosphoric acid and sodium alginate, stir at 120°C at 250 rpm for 3 h, and cool to 25°C to obtain PSA@MXene solution.
[0100] Solution 2: First, phosphoric acid, sodium alginate and urea were mixed and dissolved uniformly, stirred at 60°C for 10 minutes, and then MXene was added. After stirring at 250 rpm at 120°C for 3 hours, the mixture was cooled to 25°C to obtain a PSA@MXene solution.
[0101] Scheme 3: directly mix phosphoric acid, sodium alginate, MXene and urea, stir at 250 rpm for 3 h at 120 °C, and cool to 25 °C to obtain PSA@MXene solution;
[0102] result:
[0103] In scheme 1, the uneven dispersion of MXene will lead to the loss of surface active sites, affecting the effect of grafting phosphorylated sodium alginate onto the MXene surface;
[0104] In scheme 2, MXene is unevenly dispersed, which affects the grafting rate of phosphorylated sodium alginate on the MXene surface;
[0105] In option three, adding the raw materials together will result in poor MXene dispersion, and chemical grafting may fail or the grafting rate may be very low.
[0106] Comparative Example 3: Effect of raw materials on the preparation of flame-retardant fabrics
[0107] The specific implementation method is the same as Example 1, except that sodium alginate is replaced by chitosan aqueous solution, phosphoric acid is replaced by phosphorous acid, and urea is replaced by formaldehyde aqueous solution;
[0108] Specifically, the method for preparing a flame retardant fabric comprises the following steps:
[0109] 1. Preparation of phosphorylated chitosan modified MXene (PC@MXene)
[0110] (1) Dissolve 2 g of chitosan (CS) in 100 mL of 1% acetic acid aqueous solution and stir at 600 rpm for 0.5 h to obtain a 2% CS aqueous solution;
[0111] Add formaldehyde into deionized water and stir at 500 rpm for 5 min to obtain a formaldehyde aqueous solution with a mass concentration of 0.5 g / mL;
[0112] (2) After adding 20 mL of deionized water to MXene, the MXene was evenly dispersed with phosphorous acid in a mass ratio of MXene to phosphorous acid of 1:10, and after being evenly dispersed, the MXene was added to a 150 mL three-necked flask and stirred at 60° C. for 10 min; the CS aqueous solution and the formaldehyde aqueous solution obtained in step (1) were added to the three-necked flask respectively, and the mixture was stirred at 350 rpm at 120° C. for 3 h, and then cooled to 25° C. to obtain a reaction mixture; wherein the mass ratio of MXene, phosphorous acid, CS aqueous solution, and formaldehyde aqueous solution was 1:10:2:10;
[0113] (3) The reaction mixture obtained in step (2) was refluxed and condensed at 130° C. for 3 h, and the condensate was concentrated by rotary evaporation. The concentrate was purified and precipitated in deionized water. The precipitate was vacuum dried at 80° C. for 8 h to obtain phosphorylated chitosan modified MXene (PC@MXene) powder. The PC@MXene powder was dissolved in deionized water to obtain a PC@MXene solution with a solid content of 1.5 wt%.
[0114] 2. Preparation of flame retardant fabrics
[0115] The pretreated cotton fabric was immersed in the PC@MXene solution for 6 min and then dried at 60 °C to constant weight to obtain a flame retardant fabric (CT-MPC).
[0116] By adjusting the dosage of PC@MXene solution, cotton fabrics with flame retardant function were obtained with a weight increase of 5%, 10%, and 15% relative to the original cotton fabric, which were recorded as CT-MPC-1, CT-MPC-2, and CT-MPC-3, respectively.
[0117] Comparative Example 4: Effect of raw materials on the preparation of flame-retardant fabrics
[0118] The specific implementation method is the same as Example 1, except that sodium alginate is replaced by cellulose (particle size of 50 μm);
[0119] Specifically, the method for preparing a flame retardant fabric comprises the following steps:
[0120] 1. Preparation of phosphorylated cellulose modified MXene (PCNF@MXene)
[0121] (1) MXene and phosphoric acid were dissolved and dispersed uniformly in phosphoric acid at a mass ratio of 1:13, and after being uniformly dispersed, they were added into a 150 mL three-necked flask and stirred at 60°C for 10 min; CNF and urea were added into the three-necked flask respectively, and stirred at 250 rpm at 120°C for 3 h, and then cooled to 25°C to obtain a reaction mixture; wherein the mass ratio of MXene, phosphoric acid, CNF, and urea was 1:13:1:6;
[0122] (2) The reaction mixture obtained in step (1) was poured into 100 mL of anhydrous ethanol for purification and precipitation. The precipitate was washed with ethanol three times and then with acetone twice. The precipitate was obtained by centrifugation at 9000 r / min for 8 min. The precipitate was vacuum dried at 80 ° C for 12 h to obtain phosphorylated cellulose modified MXene (PCNF@MXene) powder. The PCNF@MXene powder was dissolved in deionized water to obtain a PCNF@MXene solution with a solid content of 1.5 wt%.
[0123] 2. Preparation of flame retardant fabrics
[0124] The pretreated cotton fabric was immersed in the PCNF@MXene solution for 6 min and then dried at 60 °C to constant weight to obtain a cotton fabric with flame retardant function (CT-MPF).
[0125] By adjusting the dosage of PCNF@MXene solution, flame-retardant cotton fabrics with weight gains of 5%, 10%, and 15% relative to the original cotton fabric were obtained, which were recorded as CT-MPF-1, CT-MPF-2, and CT-MPF-3, respectively.
[0126] Comparative Example 5: Fabric modified with MXene only
[0127] Specific implementation method The CT-MPS-2 with a weight increase of 10% relative to the original cotton fabric in Example 1 is different in that the fabric is directly modified with MXene instead of using phosphorylated sodium alginate (PSA) to modify MXene;
[0128] Specifically, the preparation method of MXene modified fabric comprises the following steps:
[0129] (1) Preparation of MXene solution
[0130] 30 mL of concentrated hydrochloric acid and 10 mL of water were mixed to obtain a 9 M hydrochloric acid solution; 2 g of lithium fluoride was added to the hydrochloric acid solution obtained above, and mixed for 5 min. 3 AlC 2 Ti was added in a mass ratio of 1:1 3 AlC 2 The powder was reacted at 40°C for 48 hours to obtain an etchant; the etchant was washed with deionized water until the solution pH = 7.0, centrifuged at 5000r / min for 10 minutes, and the upper layer of liquid was taken to obtain a MXene solution. The obtained MXene solution was added or removed from deionized water to obtain a MXene solution with a mass concentration of 15mg / mL.
[0131] (2) Calculate the amount of MXene solution prepared in step (1) required to increase the weight of the cotton fabric by 10%, then immerse the pretreated cotton fabric in the MXene solution for 6 min and dry it at 60 °C to constant weight to obtain a MXene-modified fabric.
[0132] Comparative Example 6: Phosphorylated MXene Modified Fabric
[0133] Specific implementation method The CT-MPS-2 with a weight increase of 10% relative to the original cotton fabric in Example 1 is different in that MXene is directly modified with phosphoric acid, sodium alginate and urea are not added, and other conditions remain unchanged;
[0134] Specifically, the preparation method of phosphorylated MXene modified fabric comprises the following steps:
[0135] (1) MXene and phosphoric acid were dissolved and dispersed uniformly in phosphoric acid at a mass ratio of 1:13, and after being uniformly dispersed, they were added into a 150 mL three-necked flask, stirred at 60 ° C for 10 min, then stirred at 120 ° C at 250 rpm for 3 h, and then cooled to 25 ° C to obtain a reaction mixture;
[0136] (2) The reaction mixture obtained in step (1) was poured into 100 mL of anhydrous ethanol for purification and precipitation. The precipitate was washed with ethanol three times and then with acetone twice, and centrifuged at 9000 r / min for 8 min to obtain a precipitate. The precipitate was vacuum dried at 80° C. for 12 h to obtain a phosphorylated MXene powder. The phosphorylated MXene powder was dissolved in deionized water to obtain a phosphorylated MXene solution with a solid content of 1.5 wt%.
[0137] (3) Calculate the amount of phosphorylated MXene solution prepared in the above step (2) required to increase the weight of the cotton fabric by 10%, then immerse the pretreated cotton fabric in the phosphorylated MXene solution for 6 minutes, and dry it at 60°C to constant weight to obtain phosphorylated MXene modified fabric.
[0138] Comparative Example 7: Phosphorylated Sodium Alginate Modified Fabric
[0139] Specific implementation method The CT-MPS-2 with a weight increase of 10% relative to the original cotton fabric is the same as in Example 1, except that the fabric is modified by phosphorylated sodium alginate, and MXene is not modified, and other conditions remain unchanged;
[0140] Specifically, the preparation method of phosphorylated sodium alginate modified fabric comprises the following steps:
[0141] (1) Sodium alginate (SA), urea and phosphoric acid were added to a three-necked flask in a mass ratio of 1:6:13, respectively, and the mixture was stirred at 250 rpm at 120° C. for 3 h, and then cooled to 25° C. to obtain a reaction mixture;
[0142] (2) pouring the reaction mixture obtained in step (1) into 100 mL of anhydrous ethanol for purification and precipitation, and drying the precipitate in vacuum at 80° C. for 12 h to obtain phosphorylated sodium alginate powder, and dissolving the phosphorylated sodium alginate powder in deionized water to obtain a phosphorylated sodium alginate (PSA) solution with a solid content of 1.5 wt %;
[0143] (3) Calculate the amount of the PSA solution prepared in step (2) required to increase the weight of the cotton fabric by 10%, then immerse the pretreated cotton fabric in the PSA solution for 6 minutes, and dry it at 60° C. to constant weight to obtain a phosphorylated sodium alginate modified fabric.
[0144] Comparative Example 8: Fabric modified with common flame retardant (ammonium polyphosphate)
[0145] Directly use ammonium polyphosphate to prepare ammonium polyphosphate modified fabric;
[0146] Specifically, the steps include:
[0147] (1) dissolving ammonium polyphosphate powder in deionized water to obtain an ammonium polyphosphate solution with a mass concentration of 1.5%;
[0148] (2) Calculate the amount of the ammonium polyphosphate solution prepared in the above step (1) required to increase the weight of the cotton fabric by 10%, then immerse the pretreated cotton fabric in the ammonium polyphosphate solution for 6 minutes, and dry it at 60° C. to constant weight to obtain an ammonium polyphosphate modified fabric.
[0149] The cotton fabrics obtained in Example 1 and Comparative Examples 3 to 8 were subjected to surface microscopic morphology characterization, thermogravimetric performance test, and vertical combustion performance test relative to the original cotton fabrics with different weight gain conditions. The test results are as follows:
[0150] 1. Morphology characterization
[0151] (1) CT-MPS (Example 1)
[0152] The surface microstructures of the untreated cotton fabric (CT), the flame retardant fabric obtained in Example 1, and the samples with a weight increase of 5% (CT-MPS-1), 10% (CT-MPS-2), and 15% (CT-MPS-3) relative to the original cotton fabric were characterized. The results are as follows: Figure 1 show:
[0153] Compared with the flat and smooth surface of the CT sample, the surface of the cotton fabric treated with PSA@MXene flame retardant has similar granular and flake-like substances evenly attached to the surface of the fabric. It can be seen that with the increase in weight gain, the amount of flame retardant solution attached to the cotton fiber also gradually increases, confirming that the flame retardant has been successfully finished on the fabric.
[0154] (2) CT-MPC (Comparative Example 3)
[0155] The surface microstructure of the flame retardant samples obtained in Comparative Example 3 after weight increase of 5% (CT-MPC-1), 10% (CT-MPC-2), and 15% (CT-MPC-3) relative to the original cotton fabric was characterized. The results are as follows: Figure 2 show:
[0156] The CT-MPC cotton fabric exhibits an orthogonal plain weave structure. As the weight gain of the CT-MPC cotton fabric increases, the grooves between the woven structure of the CT-MPC cotton fabric gradually become shallower and the gaps gradually decrease. As the weight gain of the CT-MPC cotton fabric increases, the surfaces of CT-MPC-2 and CT-MPC-3 show slightly rough features, and some wrinkles are formed on the fiber surface. The above results confirm that the flame retardant coating was successfully constructed on the control surface. In addition, the thickness of the PC@MXene solution of the flame retardant fabric also gradually increases with the increase of the weight of the flame retardant.
[0157] (3) CT-MPF (Comparative Example 4)
[0158] The surface microscopic morphology of the flame retardant fabrics obtained in Comparative Example 4 was characterized by adding 5% (CT-MPF-1), 10% (CT-MPF-2), and 15% (CT-MPF-3) weight to the original cotton fabric. The results showed that:
[0159] The surface of the CT sample is smooth and flat, and granular attachments appear on the surface of the cotton fabric after the PCNF@MXene flame retardant treatment. And as the weight of the flame retardant increases, the attachments on the cotton fiber surface gather more. It can be seen that the flame retardant PCNF@MXene is successfully finished on the surface of the cotton fiber.
[0160] 2. Thermogravimetric performance test
[0161] In order to evaluate the thermal degradation and thermal oxidation behaviors of the modified cotton fabrics, 2 and O 2 Thermogravimetric tests were performed on untreated cotton fabric (CT) and cotton fabrics with different flame retardant properties. The results are as follows: Figure 3 , Figure 4 And as shown in Table 1.
[0162] The TGA curve can tell the decomposition temperature range and residue amount of the sample. The DTG curve shows the rate of change of weight with time or temperature, and can be used to analyze the temperature of the maximum decomposition rate. The peak of the DTG curve is the maximum value of the weight loss rate, which corresponds to the inflection point of the TGA curve. When the physical state of the substance being tested changes, a thermal effect will occur, and a peak will appear on the DTG curve.
[0163] (1) CT-MPS (Example 1)
[0164] Thermogravimetric tests were performed on untreated cotton fabric (CT), flame retardant fabric obtained in Example 1, and samples with weight increase of 5% (CT-MPS-1), 10% (CT-MPS-2), and 15% (CT-MPS-3) relative to the original cotton fabric.
[0165] Samples in O 2 and N 2 Under this condition, the TGA curve in the range of 0 to 800°C is as follows Figure 3 As shown, it can be seen that:
[0166] The thermal decomposition of cotton fabrics in air went through three stages, with the fastest degradation temperature at around 386°C. The fastest degradation temperature of CT-MPS-1 was around 460°C, and with the increase of flame retardant content, the fastest degradation temperature of CT-MPS-3 reached about 740°C.
[0167] It can be seen that under the action of the flame retardant, the phosphorus-containing substances in it decompose and catalyze the cotton fabric and sodium alginate into carbon. In addition, the physical barrier effect of MXene isolates oxygen and delays combustion.
[0168] (2) CT-MPC (Comparative Example 3)
[0169] Similarly, the flame retardant samples obtained in Comparative Example 3 were subjected to thermogravimetric tests after the weight increase of 5% (CT-MPC-1), 10% (CT-MPC-2), and 15% (CT-MPC-3) relative to the original cotton fabric. 2 and N 2 Under this condition, the TGA curve in the range of 0 to 800°C is as follows Figure 4 shown.
[0170] Depend on Figure 4 It can be seen that the thermal decomposition of cotton fabric in air went through three stages, and the fastest degradation temperature was around 410°C. The fastest degradation temperature of CT-MPC-1 was around 470°C, and with the increase of flame retardant content, the fastest degradation temperature of CT-MPS-3 reached about 667°C.
[0171] 3. Vertical combustion performance test
[0172] Vertical burning tests were conducted on untreated cotton fabric (CT) and cotton fabric samples with different flame retardant properties. The results are as follows: Figure 5 , Figure 6 And as shown in Table 1.
[0173] (1) CT-MPS (Example 1)
[0174] The untreated cotton fabric (CT), the flame retardant fabric obtained in Example 1, and the samples with a weight increase of 5% (CT-MPS-1), 10% (CT-MPS-2), and 15% (CT-MPS-3) relative to the original cotton fabric were subjected to a vertical combustion test. The results are as follows: Figure 5 As shown, the results show:
[0175] CT-MPS-1, CT-MPS-2 and CT-MPS-3 can all achieve self-extinguishing when away from the flame. When the weight gain is only 5%, it has reached the V-0 level. As the weight gain of the flame retardant increases, the damage length of CT-MPS-1, CT-MPS-2 and CT-MPS-3 becomes shorter and shorter. Among them, the damage length of CT-MPS-3 is only 9cm. This shows that cotton fabric has significant flame retardancy after being modified by the flame retardant PSA@MXene solution.
[0176] (2) CT-MPC (Comparative Example 3)
[0177] The flame retardant samples obtained in Comparative Example 3 were subjected to vertical combustion tests after weight increase of 5% (CT-MPC-1), 10% (CT-MPC-2), and 15% (CT-MPC-3) relative to the original cotton fabric. The results are as follows: Figure 6 As shown, the results show:
[0178] CT-MPC-1 continued to burn after ignition, and when the addition amount was 10% (CT-MPC-2), the sample reached the V-0 level and achieved self-extinguishing when away from the fire.
[0179] (3) CT-MPF (Comparative Example 4)
[0180] The flame retardant fabrics obtained in Comparative Example 4 were subjected to vertical combustion tests after the weight increase of 5% (CT-MPF-1), 10% (CT-MPF-2), and 15% (CT-MPF-3) relative to the original cotton fabric. The results showed that:
[0181] Similar to the flame retardant effect of CT-MPC (Comparative Example 3), CT-MPF-1 continues to burn after ignition. When the addition amount reaches 10% (CT-MPF-2), the vertical combustion performance of the sample reaches V-0 level, and self-extinguishing has been achieved.
[0182] (4) Fabric modified with MXene only (Comparative Example 5)
[0183] In air and nitrogen atmospheres, the char formation of MXene-modified fabrics with a weight gain of 10% was approximately 3.8% and 18.2%, but due to the good thermal conductivity of MXene itself, it could not self-extinguish in the vertical combustion test and was only NR grade.
[0184] (5) Phosphorylated MXene modified fabric (Comparative Example 6)
[0185] The phosphoric acid-modified MXene-modified fabric sample with a weight gain of 10% relative to the original cotton fabric has a carbon residue rate of 4.2% and 20.6% under air and nitrogen. However, similar to Comparative Example 4, the high MXene content makes its vertical combustion performance poor.
[0186] (6) Phosphorylated sodium alginate modified fabric (Comparative Example 7)
[0187] The char residue rate of the phosphorylated sodium alginate modified fabric, which was 10% heavier than the original cotton fabric, under air and nitrogen was lower than that of other flame-retardant fabrics.
[0188] (7) Fabric modified with common flame retardant (ammonium polyphosphate) (Comparative Example 8)
[0189] In the vertical burning test, the damaged length of the ammonium polyphosphate modified fabric increased significantly, indicating that the burning continued quickly and the flame retardant effect was poor.
[0190] (8) Fabrics with a mass ratio of MXene, phosphoric acid, SA, and urea of 1:26:2:12 and 1:1:0.1:0.6 (Comparative Example 1)
[0191] When the mass ratio of MXene, phosphoric acid, SA, and urea is 1:26:2:12, it is beneficial to catalyze the carbonization of the substrate. However, although too much is easy to burn vertically, the degradation temperature of the material becomes lower, and the fabric will be degraded into carbon too early, causing more damage to the fabric.
[0192] When the mass ratio of MXene, phosphoric acid, SA, and urea is 1:1:0.1:0.6, MXene can improve the heat resistance of the material and act as a physical barrier. However, when the mass of MXene is too high relative to other raw materials, it will increase the thermal conductivity of the material and make it difficult to pass the vertical combustion test.
[0193] In order to compare the performance of samples prepared from different bio-based materials, CT-MPS-2 (Example 1), CT-MPC-2 (Comparative Example 3), CT-MPF-2 (Comparative Example 4) and Comparative Examples 5 to 8 with a flame retardant weight gain of about 10% were selected for comparison. The results are shown in Table 1:
[0194] Table 1
[0195]
[0196]
[0197] Note: NR stands for total destruction by fire, no UL-94 rating.
[0198] The results show that the residual carbon rates of CT-MPS-2, CT-MPC-2, and CT-MPF-2 under air and nitrogen are much higher than that of cotton fabric (CT). Combining the results of thermogravimetric performance tests and vertical combustion performance tests, CT-MPS-2 in Example 1 has the best flame retardant modification effect.
[0199] Furthermore, by adding an antibacterial agent to Example 1 having the best flame retardant effect, a fabric having both flame retardant and antibacterial functions was prepared.
[0200] Example 2: Preparation of fabric with both flame retardant and antibacterial functions
[0201] 1. Preparation of phosphorylated sodium alginate modified MXene (PSA@MXene)
[0202] A PSA@MXene solution with a solid content of 1.5 wt% was prepared according to the method of Example 1;
[0203] 2. Preparation of antibacterial agent
[0204] Dispersing mesoporous silica nanoparticles in chloroform, adding prickly ash essential oil and polyvinyl pyrrolidone in a mass ratio of 1:1:0.2 respectively, mixing at 600 rpm for 15 min, separating and purifying to obtain a bio-based antibacterial agent solution with a solid content of 1.5 wt%;
[0205] 3. Preparation of fabrics with both flame retardant and antibacterial functions
[0206] (1) Preparation of flame retardant and antibacterial composite solution:
[0207] A PSA@MXene solution with a solid content of 1.5 wt%, a bio-based antibacterial agent solution with a solid content of 1.5 wt%, and polyvinyl pyrrolidone were mixed in a mass ratio of 1:1:0.2 to obtain a flame retardant and antibacterial composite solution;
[0208] (2) Calculate the amount of the flame retardant and antibacterial composite solution prepared in the above step (1) required to increase the weight of the cotton fabric by 10%, then immerse the pretreated cotton fabric in the flame retardant and antibacterial composite solution in step (1) for 6 minutes, and then dry it at 60°C to constant weight to obtain a fabric with both flame retardant and antibacterial functions (CT-MPS-PEO).
[0209] Comparative Example 9: Effect of the ratio of flame retardant and antibacterial agent on the preparation of fabrics with both flame retardant and antibacterial functions
[0210] The specific method is the same as Example 2, except that the mass ratio of the PSA@MXene solution, the bio-based antibacterial agent solution, and the polyvinyl pyrrolidone is adjusted to 5:1:0.6 to prepare a fabric with both flame retardant and antibacterial functions.
[0211] Comparative Example 10: Effect of raw materials on the preparation of fabrics with both flame retardant and antibacterial functions
[0212] The specific implementation method is the same as Example 2, except that polyethylene glycol is used to replace polyvinyl pyrrolidone to prepare the antibacterial agent solution, and other conditions remain unchanged to prepare a fabric with both flame retardant and antibacterial functions.
[0213] Comparative Example 11: Effect of raw materials on the preparation of fabrics with both flame retardant and antibacterial functions
[0214] The specific implementation method is the same as Example 2, except that hexadecyltrimethylammonium bromide is used to replace polyvinylpyrrolidone to prepare the antibacterial agent solution, and other conditions remain unchanged to prepare a fabric with both flame retardant and antibacterial functions.
[0215] Comparative Example 12: Preparation of fabric with only antibacterial function
[0216] The specific implementation method is the same as Example 2, except that only the antibacterial agent solution is used, the phosphorylated sodium alginate modified MXene (PSA@MXene) is omitted, and other conditions remain unchanged to prepare a fabric with only antibacterial function.
[0217] The antibacterial performance of the cotton fabrics obtained in Example 1 and Example 2 and Comparative Examples 9 to 12 was tested respectively, and the results are shown in Table 2:
[0218] Table 2
[0219] sample Staphylococcus aureus inhibition rate (%) Escherichia coli inhibition rate (%) Example 1 28.42 20.54 Example 2 42.75 30.86 Comparative Example 9 31.63 25.22 Comparative Example 10 25.39 19.29 Comparative Example 11 23.99 17.75 Comparative Example 12 31.70 23.98
[0220] The results show:
[0221] Since the essential oil of Zanthoxylum bungeanum itself has an inhibitory effect on Staphylococcus aureus and Escherichia coli, the antibacterial effect of the fabric with both flame retardant and antibacterial functions in Example 2 on Staphylococcus aureus and Escherichia coli is better than that in Example 1.
[0222] In Comparative Example 9, when the mass ratio of PSA@MXene solution, bio-based antibacterial agent solution, and polyvinyl pyrrolidone is 5:1:0.6, the antibacterial agent content is low and the antibacterial effect is not as good as that in Example 2, but the vertical burning grade is V-0 and the flame retardant effect is better.
[0223] Comparative Example 10 uses polyethylene glycol as a dispersant. Compared with polyvinyl pyrrolidone (Example 2) as a dispersant, its adsorption capacity is weaker, and its adsorption capacity for Zanthoxylum bungeanum essential oil is slightly poor, which is not conducive to the adsorption and slow release of antibacterial substances, and the antibacterial effect is poor.
[0224] Comparative Example 11 uses hexadecyltrimethylammonium bromide as a dispersant, which has greater biological toxicity and environmental hazards compared with polyvinylpyrrolidone (Example 2);
[0225] The antibacterial effect of the fabric with only antibacterial function in Comparative Example 12 is also poorer than that in Example 2.
[0226] In summary, the ratio of the flame retardant to the antibacterial agent in Example 2 is relatively reasonable, and the flame retardant performance reaches V-0 while the antibacterial rate can also be achieved.
[0227] Example 3: Preparation of fabric with both flame retardant and electromagnetic shielding functions
[0228] A method for preparing a fabric having both flame retardancy and electromagnetic shielding functions, comprising the following steps:
[0229] (1) Preparation of MXene solution
[0230] 30 mL of concentrated hydrochloric acid and 10 mL of water were mixed to obtain a 9 M hydrochloric acid solution; 2 g of lithium fluoride was added to the hydrochloric acid solution obtained above, and mixed for 5 min.3 AlC 2 Ti was added in a mass ratio of 1:1 3 AlC 2 The powder was reacted at 40°C for 48 hours to obtain an etchant; the etchant was washed with deionized water until the solution pH = 7.0, centrifuged at 5000r / min for 10 minutes, and the upper liquid was taken to obtain a MXene solution; deionized water was added or removed from the obtained MXene solution to obtain a MXene solution with a mass concentration of 15mg / mL;
[0231] (2) Different amounts of MXene solution were sprayed on the surface of CT-MPS-2 (the flame retardant increased the weight of the original cotton fabric by 10%, the CT-MPS sample obtained in Example 1) as an enhanced electromagnetic shielding layer, and fabrics with both flame retardant and electromagnetic shielding functions were obtained with a spraying amount of 5%, 10%, 15%, and 20% relative to the original cotton fabric, which were recorded as CT-MPS-2-5%, CT-MPS-2-10%, CT-MPS-2-15%, and CT-MPS-2-20%, respectively.
[0232] The electromagnetic shielding performance of these four samples was tested, and the results are shown in Table 3:
[0233] Table 3
[0234] sample Vertical burning level Electromagnetic shielding (dB) CT-MPS-2-5% V-0 5 CT-MPS-2-10% V-0 10 CT-MPS-2-15% V-0 23 CT-MPS-2-20% V-1 28
[0235] The results show:
[0236] As the amount of MXene enhanced electromagnetic shielding layer sprayed increases, the electromagnetic shielding performance of the fabric increases from 5dB to 30dB, but the increase in MXene content will also promote the formation of a thermal conductive network, resulting in a decrease in flame retardancy. When the spraying amount relative to the original cotton fabric is 15% (CT-MPS-2-15%), the flame retardant and electromagnetic shielding properties of the fabric reach the best. Therefore, the preferred spraying amount of MXene solution is 15%.
[0237] Example 4: Preparation of fabrics with flame retardant, antibacterial and electromagnetic shielding functions
[0238] Specific implementation method The same as Example 3, except that CT-MPS-2 (the flame retardant has a 10% weight increase relative to the original cotton fabric, the CT-MPS sample obtained in Example 1) is replaced with CT-MPS-PEO (Example 2);
[0239] Specifically, the method for preparing a fabric having flame retardant, antibacterial and electromagnetic shielding functions comprises the following steps:
[0240] (1) Preparation of MXene solution
[0241] Prepare MXene solution according to the method of Example 3;
[0242] (2) Spraying MXene solution onto the surface of CT-MPS-PEO (Example 2) increased its weight by 15% relative to the original cotton fabric, and obtained a fabric having flame retardant, antibacterial and electromagnetic shielding properties, which was recorded as CT-MPS-PEO-15%.
[0243] The test results of electromagnetic shielding performance and antibacterial performance of CT-MPS-PEO-15% are shown in Table 4:
[0244] Table 4
[0245]
[0246] Therefore, the fabric CT-MPS-PEO-15% not only meets the requirements of excellent flame retardancy (vertical burning grade reaches V-0), but also has certain antibacterial properties and rich electromagnetic shielding properties.
[0247] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a flame retardant fabric, characterized in that: The steps include: (1) Mixing MXene and a phosphorylating agent in a mass ratio of 1:(1-26), heating, stirring, then adding sodium alginate and urea, continuing to heat, stir, and cool to obtain a mixture; The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12); (2) purifying the mixture and precipitating the precipitate, washing, centrifuging, and drying the precipitate to obtain a phosphorylated sodium alginate-modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate-modified MXene solution; (3) The fabric is dipped into a phosphorylated sodium alginate modified MXene solution and dried to obtain a fabric with flame retardant function.
2. The preparation method according to claim 1, characterized in that: In step (1), the phosphorylating agent is one or more of H3PO4, H3PO3, P2O5, POCl3, C6H7O3P, NH4H2PO4, (NH4)2HPO4, phosphoric anhydride, and organic phosphate.
3. The flame-retardant fabric prepared by the preparation method according to claim 1 or 2.
4. A method for preparing a fabric having both flame retardant and antibacterial functions, characterized in that: The preparation method comprises mixing a phosphorylated sodium alginate modified MXene solution, an antibacterial agent solution, and polyvinyl pyrrolidone in a mass ratio of (1-5):(1-5):(0.2-1) to obtain a flame retardant and antibacterial composite solution, and then immersing the fabric in the flame retardant and antibacterial composite solution, and drying the mixture to obtain a fabric having both flame retardant and antibacterial functions. The method for preparing the phosphorylated sodium alginate modified MXene solution comprises the following steps: (1) Mixing MXene and a phosphorylating agent in a mass ratio of 1:(1-26), heating, stirring, then adding sodium alginate and urea, continuing to heat, stir, and cool to obtain a mixture; The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12); (2) The mixture is purified and precipitated, and the precipitate is washed, centrifuged, and dried to obtain phosphorylated sodium alginate modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate modified MXene solution.
5. The preparation method according to claim 4, characterized in that: The method for preparing the antibacterial agent solution comprises the following steps: Dispersing mesoporous silica in a solvent, then adding prickly ash essential oil and polyvinyl pyrrolidone, mixing, separating and purifying, and obtaining an antibacterial agent solution; The mass ratio of the mesoporous silica, the prickly ash essential oil and the polyvinyl pyrrolidone is 1:(0.5-3):(0.05-0.2).
6. The fabric having both flame retardant and antibacterial functions prepared by the preparation method according to claim 4 or 5.
7. A method for preparing a multifunctional fabric having flame retardancy, antibacterial properties and electromagnetic shielding properties, characterized in that: The preparation method is to coat the surface of the fabric with flame retardant and antibacterial functions as claimed in claim 6 with a MXene solution as an enhanced electromagnetic shielding layer to obtain a multifunctional fabric with flame retardant, antibacterial and electromagnetic shielding functions.
8. The multifunctional fabric having flame retardancy, antibacterial properties and electromagnetic shielding properties prepared by the preparation method according to claim 7.
9. Application of the flame-retardant fabric of claim 3, the flame-retardant and antibacterial fabric of claim 6, and the flame-retardant, antibacterial and electromagnetic shielding multifunctional fabric of claim 8 in the fields of home furnishing, medical protection, and electronic communication equipment protection.
10. A method for simultaneously improving the flame retardant properties, antibacterial properties, and electromagnetic shielding properties of a fabric, characterized in that: The steps include: (1) Mixing MXene and a phosphorylating agent in a mass ratio of 1:(1-26), heating, stirring, then adding sodium alginate and a catalyst, continuing to heat, stir, and cool to obtain a mixture; The mass ratio of the MXene, phosphorylating agent, sodium alginate and urea is 1:(1-26):(0.1-2):(0.6-12); (2) purifying the mixture and precipitating the precipitate, washing, centrifuging, and drying the precipitate to obtain a phosphorylated sodium alginate-modified MXene, which is then dissolved in water to obtain a phosphorylated sodium alginate-modified MXene solution; (3) mixing a phosphorylated sodium alginate modified MXene solution, an antibacterial agent solution, and polyvinyl pyrrolidone in a mass ratio of (1-5):(1-5):(0.2-1) to obtain a flame retardant and antibacterial composite solution, and then immersing the fabric in the flame retardant and antibacterial composite solution, and drying to obtain a fabric having both flame retardant and antibacterial functions; (4) MXene solution is coated on the surface of the fabric with flame retardant and antibacterial functions as an enhanced electromagnetic shielding layer to obtain a multifunctional fabric with flame retardant, antibacterial and electromagnetic shielding functions.
Citation Information
Patent Citations
A high-strength flame-retardant MXene / phosphorylated cellulose fiber composite film and its preparation method
CN115322443B
High-strength flame-retardant MXene / phosphorylated cellulose filament composite film and preparation method thereof
CN115322443A
Preparation method of self-repairing hydrogel flame-retardant coating
CN116355478A
Flame-retardant self-repairing coating and fire early warning application thereof
CN116516673A
High-strength flame-retardant mxene / phosphorylated cellulose fibril composite film and preparation method therefor
WO2024060807A1
Cited By
Preparation process of organic fireproof flame retardant
CN120248219A
Electromagnetic shielding flame-retardant fabric and preparation method thereof
CN120537118A
Electromagnetic shielding flame resistant fabric and method of making same
CN120537118B
Preparation method and application of high-stability flexible electronic fabric
CN121228540A